Entrepreneurial Spirit of Domestic Business Actor Digital Marketing for MSMEs in Bandung City - Heri Erlangga; Yanti Purwanti; Yayan Mulyana (Pendidikan Administrasi Perkantoran, Universitas Negeri Makassar, 2021)
In the process of its development, MSMEs face various obstacles both in terms of human resources, finance, and markets. However, although MSMEs have many obstacles in developing them, the spirit of business actors is one of the keys to success in trying to make MSMEs continue to advance and be able to compete with other similar businesses. The method used in this research is qualitative. This method is based on a holistic and complete appreciation of human behavior. In this regard, entrepreneurship is a behavioral symptom. All activities that take place are researched as they are (natural setting) and explored through a deep appreciation method (verstehen) and look for what values are inherent in the entrepreneurial spirit armed with the experience and knowledge possessed. The targeted outputs are international journals indexed by Scopus, Sinta, International Proceedings and Monograph Books from research results. TKT (Technology Readiness Level) is already in stage 3, namely the proof-of-concept of functions and characteristics already analytically and experimentally, namely the Research Design and Methodology has been prepared, the design methodology used to answer research questions has also been prepared, the design determination sampling, and data collection needs as well as data collection techniques have been prepared, the adequacy and completeness of the data has been determined. The technical evaluation and prediction of results have been carried out, scenarios and alternatives for completeness of data have been prepared and R&D designs have been made.